Definitional dilemma of “terrorism” under international law - Muhammad Imran,; Rohaida Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Terrorism is not a domestic issue but is instead a global phenomenon. The changing form of terrorism is going to be complex day by day. Every State is facing terrorism, and no State is immune to this disease. None the least, the lack of a universally accepted definition of terrorism is a significant hindrance in developing effective international counter terrorism strategies. The 9/11 attacks in the US have unavoidably shaped the fight against by demanding a rapid and unified reaction from the international community. This Paper examines the meaning of terrorism and also evaluates the definitions of terrorism presented by various scholars. It also highlights the hurdles which are hindering in attaining a universally accepted definition of terrorism. Moreover, the definitions of terrorism by the International bodies such as the United Nations General Assembly, the Security Council, the International Court of Justice and the International Criminal Court are also analysed. The analysis provides a foundation for any future evaluation on definition of terrorism under any domestic counter terrorism laws. This Paper concludes that a universally accepted definition of terrorism is necessary to help in curbing the issue of terrorism globally or domestically.